2008
DOI: 10.1111/j.1752-0606.2008.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the Self and Posttraumatic Symptomatology Among ex‐POWs and Their Wives

Abstract: War captivity is a highly traumatic experience which sometimes has deleterious effects on both ex-POWs and their wives. This study examined the relationships between posttraumatic stress disorder (PTSD) symptoms and differentiation among male ex-prisoners of war (ex-POWs; n = 103), their wives (n = 82), and comparable controls. Results show that ex-POWs and their wives endorsed more PTSD symptoms than controls. Ex-POWs endorsed more cut-off and fusion than controls, while their wives endorsed only more fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…We also examined whether gender modified the main effect of country (or culture). Next, as differentiation of self was found to be negatively associated with psychological and physical health (e.g., Solomon, Dekel, Zerach, & Horesh, ), and specifically with anxiety (e.g., Peleg & Rahal, ), our third hypothesis suggested a negative relationship between differentiation of self, trait anxiety and somatic symptoms. Finally, we examined differences in levels of trait anxiety and somatic symptoms between the four cultural groups.…”
Section: Differentiation Of Selfmentioning
confidence: 86%
“…We also examined whether gender modified the main effect of country (or culture). Next, as differentiation of self was found to be negatively associated with psychological and physical health (e.g., Solomon, Dekel, Zerach, & Horesh, ), and specifically with anxiety (e.g., Peleg & Rahal, ), our third hypothesis suggested a negative relationship between differentiation of self, trait anxiety and somatic symptoms. Finally, we examined differences in levels of trait anxiety and somatic symptoms between the four cultural groups.…”
Section: Differentiation Of Selfmentioning
confidence: 86%
“…There is an increasing body of evidence from a number of countries to suggest that partners are affected by living with a veteran who is experiencing symptoms of PTSD/traumatization. Spouses have been found to experience high levels of stress, depression (Manguno‐Mire et al., ), symptoms of PTSD, anxiety (Westerink & Giarratano, ), adjustment disorders, relationship dissatisfaction (Lambert, Engh, Hasbun, & Holzer, ), burnout/caregiver burden (Klarić et al., ; Solomon, Dekel, Zerach, & Horesh, ), and more somatic problems (Dirkzwager, Bramsen, Ader, & van der Ploeg, ). More recently in the United Kingdom, partners of veterans were found to report difficulties with alcohol, depression, generalized anxiety disorder and probable PTSD (Murphy, Palmer, & Busittil, ).…”
Section: Communication and Empathymentioning
confidence: 99%
“…When partner distress is identified, the question arises as to the antecedent of this distress. Is this partner distress and possible PTSD secondary to the impact of living with and caring for someone with war zone-related physical and/or psychiatric disabilities (Monson, Taft, & Fredman, 2009;Solomon, Dekel, Zerach, & Horesh, 2009) or related to their own prior trauma experiences (Melvin et al, 2012) or secondary to their victimization at the hands of their loved one for whom they are also the caregiver? In a study by Manguno-Mire et al (2007), over 60% of the partners studied reported that their partner (male combat veterans with PTSD) "demonstrated a physical threat to their well-being" (p. 76).…”
Section: Introductionmentioning
confidence: 99%